Pengembangan Pekarangan Produktif untuk Mendukung Ketersediaan Sayuran Organik di Tingkat Rumah Tangga: Pengabdian - Ni Putu Sukanteri; Putu Lasmi Yulianti Sapanca (Jurnal Pengabdian Masyarakat dan Riset Pendidikan, 2025)
Yard land is one of the important sectors in supporting food security, environmental sustainability, and improving family welfare and family food provision. The purpose of implementing community service is to empower communities to utilize yard land as a source of organic horticulture-based food production. Increase community knowledge and skills in organic plant cultivation techniques, such as making compost, botanical pesticides, and environmentally friendly plant management. Create productive yards that support household food security and have the potential to become an additional source of family income. The implementation of community service was carried out in Megati Village, Tabanan Bali. Community service activities were carried out in three stages, namely socialization, training and mentoring which showed that farmers had the knowledge and skills to increase the use of organic inputs in family food crop production by 100%.